Aid and government fiscal behaviour: What does the evidence say? - Oliver Morrissey (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Donors are concerned about how their aid is used, especially how it affects fiscal behaviour by recipient governments. This study reviews the recent evidence on the effects of aid on government spending and tax effort in recipient countries, concluding with a discussion of when (general) budget support is a fiscally efficient aid modality. Severe data limitations restrict inferences on the relationship between aid and spending, especially as the government is not aware of all the aid available to finance the provision of public goods. Three generalizations are permitted by the evidence: aid finances government spending; the extent to which aid is fungible is over-stated and even where it is fungible this does not appear to make the aid less effective; and there is no systematic effect of aid on tax effort. Beyond these conclusions the fiscal effects of aid are country-specific.
Keywords: E62; F35; 330; Aid; fiscal effects; fungibility; government spending; taxation; Entwicklungshilfe; Öffentliche Ausgaben; Steuereinnahmen; Entwicklungsländer